2020
DOI: 10.1155/2020/6660611
|View full text |Cite
|
Sign up to set email alerts
|

Transient Dexmedetomidine Bolus-Induced Excessive Urination Intraoperatively in a 68-Year-Old Male

Abstract: Excessive urination can be a perioperative challenge for providers due to the possibility of secondary hypernatremia. Dexmedetomidine has previously been reported by several groups to induce a polyuric-like syndrome; however, the exact mechanism in humans remains unclear. In this report, we discuss a case of intraoperative, transient dexmedetomidine bolus-induced excessive urination and suggest a potential mechanism by which this may occur in a subset of the population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
(3 reference statements)
0
3
0
Order By: Relevance
“…Polyuria in adults is either due to the excretion of nonabsorbable solutes including glucose (solute diuresis) or following the excretion of water from abnormalities in the production of arginine vasopressin or responsiveness of the renal system (water diuresis). [ 2 ] There is a plethora of differential diagnoses for polyuria in neurosurgical patients [ Figure 1 ].…”
mentioning
confidence: 99%
“…Polyuria in adults is either due to the excretion of nonabsorbable solutes including glucose (solute diuresis) or following the excretion of water from abnormalities in the production of arginine vasopressin or responsiveness of the renal system (water diuresis). [ 2 ] There is a plethora of differential diagnoses for polyuria in neurosurgical patients [ Figure 1 ].…”
mentioning
confidence: 99%
“…While the diagnosis of DI was established, the cause originally remained unclear. Several studies have noted anecdotally that surgeries involving the central nervous system are more likely to result in dexmedetomidine-induced polyuria, likely due to the fact that AVP is released by the posterior pituitary gland [10][11][12]. However, polyuria has also been observed in a wide variety of patients receiving dexmedetomidine including, patients in their sixties undergoing orthopaedic surgery, otolaryngologic surgery, and a 32-year-old male in the ICU for burns [12][13][14].…”
mentioning
confidence: 99%
“…Several studies have noted anecdotally that surgeries involving the central nervous system are more likely to result in dexmedetomidine-induced polyuria, likely due to the fact that AVP is released by the posterior pituitary gland [10][11][12]. However, polyuria has also been observed in a wide variety of patients receiving dexmedetomidine including, patients in their sixties undergoing orthopaedic surgery, otolaryngologic surgery, and a 32-year-old male in the ICU for burns [12][13][14]. A literature review found that the renal effects of dexmedetomidine on patients undergoing CABG surgery have been examined with an experimental trial.…”
mentioning
confidence: 99%